2001
DOI: 10.1002/mc.1025
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of p27 protein expression with HER‐2/neu expression in breast cancer

Abstract: Strong expression of human epidermal growth factor receptor 2 (HER-2)/neu in breast cancer has been associated with poor prognosis. Reduced expression of p27(Kip1), a cyclin-dependent kinase inhibitor, correlates with poor clinical outcome in breast cancer. In this study, we provide a correlation between these two important prognostic markers in patients with breast cancer. Breast tumor screening using immunohistochemistry indicated that downregulation of p27 correlated with HER-2/neu overexpression in studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 31 publications
4
29
1
Order By: Relevance
“…43 A study of 51 primary breast carcinomas showed that all the tumors that overexpressed HER2 had low levels of p27 Kip1 protein. 44 These studies strongly indicate that HER2 overexpression correlates tightly with decreasing p27 Kip1 expression.…”
Section: Introductionmentioning
confidence: 81%
“…43 A study of 51 primary breast carcinomas showed that all the tumors that overexpressed HER2 had low levels of p27 Kip1 protein. 44 These studies strongly indicate that HER2 overexpression correlates tightly with decreasing p27 Kip1 expression.…”
Section: Introductionmentioning
confidence: 81%
“…Akt is activated in HER2-amplified breast cancers (reviewed above) and activated Akt phosphorylates p27 inhibiting its function by excluding it from the nucleus (Liang et al, 2002;Shin et al, 2002;Viglietto et al, 2002). Several clinical studies have also established that HER2-overexpressing breast cancers have reduced p27 expression compared with other types of breast cancers (Newman et al, 2001;Loden et al, 2003;Spataro et al, 2003). HER2 mediates p27 degradation likely through mechanisms that involve MAPK (Yang et al, 2000;Donovan et al, 2001;Lenferink et al, 2001).…”
Section: Cell Cycle Deregulationmentioning
confidence: 99%
“…The general immunohistochemical staining scheme was performed as described previously (Newman et al, 2001). Antibody detection was performed with the ABC substrate kit (Vector Laboratories, Burlingame, CA, USA), and slides were counterstained with hematoxylin.…”
Section: Tumor Growth In Nude Micementioning
confidence: 99%